Towards enhancing the detection of adulteration in bioactive food products - Charles Odilichukwu R. Okpala (Journal of Food Bioactives, 2019)
This contribution aims to add a voice towards enhancing the detection of adulteration in bioactive food products. Bioactive foods—strongly associated with plant-based chemical compounds, have been shown to boost human immune function and promote health/wellbeing. On the other hand, adulteration generally makes food products to fall short of legal standards, become impure, unsafe and not wholesome. Given that food products can get adulterated either accidentally, intentionally, metallically or naturally, foods that contain bioactive compounds will not be exempted. Adulteration and adulterants therefore pose serious danger to both authenticity and quality of bioactive foods. Considering this challenge, rapid detection methods are needed to enhance the authenticity of bioactive product quality as well as consumer confidence/safety.